Improving higher education by linking research with teaching and learning processes - Juliana Schlicht, Juliana Schlicht; Klauser, Fritz (South African Journal of Higher Education, 2016)
Improving the quality of teaching and learning in higher education is a current objective in the academic discourse in Germany as well as in South Africa. Research-Based Learning (RBL) is meant to be an effective approach towards enhancing the students’ academic capability. This article illustrates how RBL could be explored in order to contribute to the quality objective in higher education. It aims at focusing on the following questions: What is RBL about? What is an appropriate organisational structure for research-based learning activities? What are guiding principles of linking research activities with academic teaching and learning? How can the research-based approach affect students’ performance, motivation and learning success?